A STUDY ON USING SCAFFOLDED READING EXPERIENCE STRATEGY IN TEACHING READING DESCRIPTIVE TEXTS - Ridha Aryani; Supriusman Supriusman; Erni Erni (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2021)
Abstract: The purpose of this study was to determine how effective the Scaffolded Reading Experience Strategy is in teaching students to read descriptive texts. The analysis used in this research was descriptive. The population of this research was all the first year students of SMA N 1 Reteh in the 2019/2020 Academic Year and one teacher. The sample for this research was 34 students from X MIPA 2 class who had been selected by using the cluster-random-sampling technique. A questionnaire and an interview were used to collect data. The questionnaire consisted of 10 statements and the interview consisted of 10 questions. Based on the result of the questionnaire, the mean score is 4.05, which means that the use of Scaffolded Reading Experience influenced by reading activity in the learning process in English class is high. Based on the result of the interview, the teaching outcomes which used the Scaffolded Reading Experience Strategy were good. The teacher said that the Scaffolded Reading Experience Strategy was easy to use and helped the students to understand the descriptive text more easily. Following comprehension, the teacher stated that some of the students could create their own descriptive text, though some students still struggled with writing the text. But after the students asked for re-explanation, the teacher explained again until the students understood a little more. The teacher thought the quality was good. The teacher stated that she would use the Scaffolded Reading Experience Strategy as her first choice in the classroom teaching and learning process and that she would recommend the Scaffolded Reading Experience Strategy to her peers for teaching other subjects.Key Words: Using, Scaffolded Reading Experience Strategy, Reading, Descriptive Text.